1993
DOI: 10.1152/ajpcell.1993.265.1.c178
|View full text |Cite
|
Sign up to set email alerts
|

Microprobe analysis of Tc-MIBI in heart cells: calculation of mitochondrial membrane potential

Abstract: Hexakis (2-methoxyisobutylisonitrile) technetium-99m (99mTc-MIBI) is a gamma-emitting radiopharmaceutical probe currently in clinical use to evaluate myocardial perfusion. Biochemical and cellular pharmacological studies have suggested that Tc-MIBI, a lipophilic cation, is sequestered in mitochondria in response to transmembrane potentials. To assess directly the subcellular distribution of the probe in heart tissue, cultured chick heart cells were analyzed by electron-probe X-ray microanalysis (EPXMA) followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 18 publications
0
29
0
5
Order By: Relevance
“…In isolated mammalian mitochondria from liver and brain under state 4 conditions, ΔΨ m values were measured ≥150 mV, often exceeding 200 mV (Nicholls 1974; Labajova et al 2006; Cossarizza et al 1996; Barger et al 2003; Shears and Kirk 1984; Brand et al 1988; da Silva et al 1998; Moreira et al 2001). In contrast, the majority of studies performed in a more physiological context with a variety of intact mammalian cells or even intact organs showed lower ΔΨ m values in the range of 80 to 140 mV (Wan et al 1993; Zhang et al 2001; Brand and Felber 1984; Backus et al 1993; Porteous et al 1998), with few studies reporting higher values between 140 – 161 mV (Nicholls 2006; Hoek et al 1980; Brand and Felber 1984; Porteous et al 1998; Nobes et al 1990; Cortese 1999). This discrepancy may be explained by differences in the regulation of OxPhos activity in higher organisms.…”
Section: A Mitochondrial Perspective On Reperfusion Injurymentioning
confidence: 97%
“…In isolated mammalian mitochondria from liver and brain under state 4 conditions, ΔΨ m values were measured ≥150 mV, often exceeding 200 mV (Nicholls 1974; Labajova et al 2006; Cossarizza et al 1996; Barger et al 2003; Shears and Kirk 1984; Brand et al 1988; da Silva et al 1998; Moreira et al 2001). In contrast, the majority of studies performed in a more physiological context with a variety of intact mammalian cells or even intact organs showed lower ΔΨ m values in the range of 80 to 140 mV (Wan et al 1993; Zhang et al 2001; Brand and Felber 1984; Backus et al 1993; Porteous et al 1998), with few studies reporting higher values between 140 – 161 mV (Nicholls 2006; Hoek et al 1980; Brand and Felber 1984; Porteous et al 1998; Nobes et al 1990; Cortese 1999). This discrepancy may be explained by differences in the regulation of OxPhos activity in higher organisms.…”
Section: A Mitochondrial Perspective On Reperfusion Injurymentioning
confidence: 97%
“…Studies based on isolated mitochondria or reconstituted CcO vesicles showed high ΔΨ m values of 180-220 mV (e.g., Cossarizza et al, 1996; Nicholls and Ferguson, 1992; Steverding and Kadenbach, 1991), but they may not represent physiological conditions because the phosphorylation state was not preserved during mitochondria isolation (discussed in Hüttemann et al, 2008). Other studies performed under more physiological conditions reported ΔΨ m values from 80-140 mV in perfused rat hearts, intact cultured fibroblasts, neuroblastoma cells, lymphocytes, embryonic heart cells, and osteocarcoma cells (Backus et al, 1993; Brand and Felber, 1984; Porteous et al, 1998; Wan et al, 1993; Zhang et al, 2001). Thus, the maintenance of physiologically low ΔΨ m values avoids excessive generation of ROS but provides the full capability to produce ATP because maximal rates of ATP synthesis by ATP synthase occur at physiological ΔΨ m values of 100-120 mV (Kaim and Dimroth, 1999).…”
Section: To the Next Level: A Proposal For The Regulation Of Mitocmentioning
confidence: 98%
“…Other investigators using the related technique of electron probe microanalysis have reported that Tc can be detected at the subcellular level within mitochondria in animal cells, but only after cultured chick embryonic heart cells were directly bathed in Tc-MIBI at concentrations of Tc much higher than is achieved at the cellular level in clinical nuclear medicine practice, and then thinly sectioned [30]. With ongoing evolution of XFM techniques, including the development of tomographic analysis [31], we hope to eventually be able to confidently identify the location of intracellular Tc in samples subjected to minimal preparation.…”
Section: Discussionmentioning
confidence: 99%